Physicochemical, nutritional, and antioxidant characteristics of the fruit of Ehretia tinifolia - Juan Fernando Pío-León; Sylvia Páz Díaz-Camacho; Mercedes G. López; Julio Montes-Avila; Gabriela López-Angulo; Francisco Delgado-Vargas (Revista Mexicana de Biodiversidad)
Physicochemical characteristics of Ehretia tinifolia L. fruit are presented for the first time. The fruit of this plant is a small drupe of 8 mm diameter and weighs 0.2 g. Its pulp is slightly acidic (pH 5.8) with a high ratio of soluble solids (11 ºBrix) to acidity (0.1%). The antioxidant activity of E. tinifolia fruits (DPPH, 303.8 mg EVC/100 g f.w.; ABTS, 84.1 mg EVC/100 g f.w.; DPPH, ABTS and EVC mean 1,1-diphenyl-2-picrylhydrazyl, 2,2’-azino-bis(3- ethylbenzothiazolin-6-sulfonate) diammonium salt, and equivalents of vitamin C, respectively) was similar or higher than reported for several tropical fruits (e.g. orange, guava, and prickly pear). Ehretia tinifolia fruit has a high content of ash (12.6 mg/100 g d.w.). The edible portion is an important source of selenium (0.1 mg/100 g d.w.) and total fatty acids were 834.8 mg/100g d.w.; the main fatty acids were palmitic (27.6%), linoleic (26.4%), linolenic (18.1%), and oleic (17.6%). The content of fatty acids of seeds was 5 137.5 mg/100 g d.w., with linoleic (54.3%), oleic (22.9%), and palmitic (12.7%) as main components.